CHILD STUDY PROGRAM APPLICATION FOR INTELLIGENT CHILDREN AGES 3 TO 5 YEARS USING Macromedia Flash MX 2004 - Melas Priya Utami; Ristyawati Ristyawati., SKom., MMSI (Jurnal Sistem Informasi, 2008)
Multimedia is a combination of the components of the information in the form of text, images, sound, animation and video together in a computer to be stored, processed and presented both linear and interactive. An application that contains only one component can still be called multimedia. Application Intelligent Child Learning Program is an application that provides information about children's learning, among others; learning to count, identify shapes, letters and colors especially for children ages 3 to 5 years. In this application there is animation, images, sounds and music. With music, kids can channel his emotions in a positive way so as to give encouragement to yourself to do something good and useful. In this case the motivation to give hope, strength and optimism that have a fighting spirit to do a certain activity, such as learning.